2015
DOI: 10.1002/mrm.26064
|View full text |Cite
|
Sign up to set email alerts
|

Generalization of intravoxel incoherent motion model by introducing the notion of continuous pseudodiffusion variable

Abstract: The GIVIM model has the ability to better describe multicomponent perfusion without lengthening acquisition time and knowing in advance the number and/or the variety of perfusion components. Magn Reson Med 76:1594-1603, 2016. © 2015 International Society for Magnetic Resonance in Medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…Further, the exact nature of the IVIM signal is not well understood and is a hot current research topic. For example, flow-compensated diffusion gradients, [132][133][134][135][136] extension of the current model, 38,137 and anisotropy studies [138][139][140] have been used to gain insight into the nature of the IVIM perfusion signal. Importantly, an already relatively large number of clinical studies have shown promising results for application in disease diagnosis, follow-up, and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the exact nature of the IVIM signal is not well understood and is a hot current research topic. For example, flow-compensated diffusion gradients, [132][133][134][135][136] extension of the current model, 38,137 and anisotropy studies [138][139][140] have been used to gain insight into the nature of the IVIM perfusion signal. Importantly, an already relatively large number of clinical studies have shown promising results for application in disease diagnosis, follow-up, and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…16,19 4 | RESULTS Figure 2 depicts one volunteer's normalized BP70 DW signal value at each b-value and the signal fitting curves derived from the GIVIM, the GIVIM-GMM and the triexponential model. In order to overcome the excessive dependence on initial value and the premature local extremum and to accelerate the LM algorithm, particle swarm optimization (PSO) was introduced.…”
Section: Fitting Methodsmentioning
confidence: 99%
“…19 like the estimation of the distribution function. 19 like the estimation of the distribution function.…”
Section: F I G U R Ementioning
confidence: 99%
See 2 more Smart Citations